Prevalence, Infectivity, and Associated Risk Factors of Hepatitis B Virus among Pregnant Women in Yirgalem Hospital, Ethiopia: Implication of Screening to Control Mother-to-Child Transmission - Anteneh Amsalu; Getachew Ferede; Setegn Eshetie; Agete Tadewos; Demissie Assegu (Journal of Pregnancy)
Background. Hepatitis B surface antigen (HBsAg) and hepatitis B e antigen (HBeAg) positive mother has up to 90% likelihood of mother-to-child transmission (MTCT) of hepatitis B virus (HBV) to newborns in the absence of any prophylaxis or antiviral therapy utilization. However, routine antenatal screening and intervention strategies are not yet practiced in Ethiopia. Therefore, this study was conducted to determine the prevalence, infectivity, and associated risk factors of HBV among pregnant women. Methods. A cross-sectional study was conducted from October 2015 to August 2016 in Yirgalem Hospital. A total of 475 pregnant women were recruited, and data on sociodemography and potential risk factors were collected using a structured questionnaire. In addition, blood samples were tested for HBsAg, and HBsAg positive samples were retested for HBeAg using commercially available strip test. The status of HIV was collected from the records. Results. The seroprevalence of HBsAg was 34 (7.2%), of whom 13 (38.8%) were positive for HBeAg. The prevalence of HIV infection was 10.1% (48/475). Ten out of 34 HBV positive cases (29.4%) were coinfected with HIV. The overall HBV/HIV coinfection rate was 2.1% (10/475). Women with history of multiple sexual partners and being HIV positive were significantly associated with HBsAg positivity. Among the study participants, 35.4% were aware of MTCT of HBV and only 12 (2.5%) have taken HBV vaccine. Conclusions. High prevalence of HBsAg and HBeAg as well as low awareness and practices of HBV prevention methods suggests that perinatal transmission of HBV might be the prevailing mode of HBV transmission in the study area. Thus, screening of all pregnant women, particularly those who had history of multiple sexual partners and HIV coinfection, and provision of health education about HBV prevention methods are inevitable.